STRATEGI FILANTROPI ISLAM DOMPET DHUAFA DIY DALAM MEMBANGUN LITERASI DAN SDM PENDIDIKAN MELALUI PROGRAM SEKOLAH LITERASI INDONESIA - Fathur Rahmansyah, Hidayat Wira; Annisa Aulia, Nur (LPPM STAI Muhammadiyah Probolinggo, 2025)
Indonesia's low literacy scores in PISA 2022 (359 points) necessitate Islamic philanthropy institutions' strategic involvement in building sustainable literacy ecosystems. This study aims to analyze Dompet Dhuafa DIY's Islamic philanthropy strategies in developing literacy and educational human resources through the Indonesia Literacy School Program (SLI), and evaluate program sustainability models through ASPIRASI. A qualitative descriptive research method was employed through in-depth interviews with DD DIY managers, program documentation analysis, and indirect observation. Data were analyzed using Miles & Huberman model with source triangulation. Results show that SLI successfully established literacy ecosystems in 12 partner schools through teacher empowerment strategies, resulting in collaborative book publications by 25 teachers and ASPIRASI formation as sustainability platform. The program transformed teachers from knowledge consumers to literacy knowledge producers. The study concludes that SLI success depends on synergy between Islamic philanthropy, teacher empowerment, and community strengthening through ASPIRASI social networks ensuring long-term program impact sustainability